Digital Transformation of Cooperatives in Indonesia: A Descriptive Qualitative Study of Cooperatives in Lampung Province - Ananto Triwibowo; Muhammad Mujib Baidhowi; M. Arif Budiman Kasim; Abizar; Mawardi Mawardi; Jati Imantoro (Nuban Jagadhita Centre, 2026)
Objective: This study aims to analyze the current state, driving and inhibiting factors, impacts, and patterns of digital transformation among cooperatives in Lampung Province, Indonesia, as part of the broader effort to modernize cooperative institutions in the digital economy. Method: A descriptive qualitative approach was employed to capture the complexity of digital transformation within cooperatives. Data were collected from seven cooperatives through in-depth interviews with 21 key informants, participatory observation, and document analysis. The data were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. Results: The findings reveal that digital adoption among cooperatives remains uneven, with an average digitalization index of 51.8%, indicating an early transition toward digital cooperative models. Digital member management systems showed the highest adoption rate, while digital annual meetings and e-commerce platforms remained limited. The main drivers of digital transformation include government support programs, competitive pressure from fintech institutions, and visionary leadership. Conversely, barriers consist of limited digital human resources, inadequate technological infrastructure, organizational resistance to change, and low digital literacy among members. The study also identifies four distinct patterns of cooperative digital transformation: Digital Pioneers, Selective Adopters, Reluctant Followers, and Passive Resistance. Furthermore, digitalization improves operational efficiency and service reach but may reduce social interaction and cooperative solidarity if not managed carefully. Implications: The findings suggest the need for differentiated digitalization policies, continuous digital capacity building, and inclusive transformation strategies that preserve cooperative values while enhancing technological competitiveness Novelty: This study contributes to the literature by proposing a contextual typology of cooperative digital transformation grounded in empirical evidence from Indonesian cooperatives and by highlighting the tension between digital efficiency and the preservation of cooperative social values, an aspect underexplored in prior research.